Is there any role of post operative antibiotics in reducing secondary haemorrhage after tonsillectomy - Kamal, Mohammad Shah; Farzana, Rubina; Tariq, Ahmed; Humayun, Abu Hena Mohammad Parvez (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective: To compare with and without the antibiotic therapy in reducing post-tonsillectomy secondary haemorrhage. Method: A prospective study was conducted at Shaheed Shamsuddin Ahmed Hospital, Sylhet from April 2010 to April 2012. 170 patients who underwent tonsillectomy divided into two groups randomly each consisting of 85 patients. In group A (intervention group) - antibiotic was given post-operatively, while in group B (control group) - no antibiotic was given. Postoperative follow-up was done till the tonsillar fossa healed. Results: Among 170 patients 61.18% were female and 38.82% were male, mean age was 21.58 years. One patient from antibiotic group had secondary haemorrhage (1.18%), while no haemorrhage was observed in non- antibiotic group. Secondary haemorrhage rate was 0.59% in total study population. Conclusion: The study showed that antibiotic did not have any significant role in reducing the post-tonsillectomy secondary haemorrhage DOI: http://dx.doi.org/10.3329/bjo.v18i2.12009 Bangladesh J Otorhinolaryngol 2012; 18(2): 166-170